(untitled) (Research, Society and Development, 2022)
Objective: To analyze and synthesize the main immunological mechanisms related to greater severity or worse outcome in pregnant women infected with SARS-CoV-2. Methods: This is a systematic literature review that was performed by searches on Medline (by PubMed), from October 2021 to January 2022, using the descriptors Pregnancy complications; Immunological Factors; SARS-CoV-2, Covid-19, which aimed to answer the question: “Which immunological mechanisms are related to greater severity or worse outcome in pregnant women infected with SARS-CoV-2?”. Original manuscripts, written in English language and published from 2020 onwards were chosen. Reviews or meta-analyses, editorials and duplicate titles were excluded. The search resulted in 189 articles, of which 11 were selected for matching the eligibility criteria. Results: Changes were found in the immunological functioning of the pregnant organism that may predispose the pregnant woman to a greater susceptibility to SARS-CoV-2 infection and to a more severe course of the disease. These alterations include reduced levels of Natural Killer cells and T helper cells type 1, in addition to an increase in the hyperinflammatory state related to excessive activation of the complement system and an increase in pro-inflammatory cytokines, such as interleukin-6 and α tumor necrosis factor. Besides the increase in angiotensin-converting enzyme 2 in maternal circulation leads to increased viral binding in the host cell and infectivity. Conclusion: Due to the impact that immunological mechanisms have on the evolution of COVID-19 disease on maternal health, it is evident the importance of identifying the elevation of these immunological biomarkers, which can help in the prediction of maternal prognosis and in the definition of appropriate early treatment.